2019
DOI: 10.3390/ani9080501
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Response in Dogs Naturally Infected by L. infantum Treated with a Nutritional Supplement

Abstract: The use of nutraceuticals as immunomodulators in the treatment of visceral leishmaniasis has generated interest in the current approaches to treat the disease. In this clinical and immunological study, we investigated whether the administration of a nutritional supplement mediates the immune-modulatory response in canine leishmaniosis (CL) and improves the clinical outcome of the disease. With this purpose, we analysed T lymphocyte subsets in peripheral blood (PB) of 12 dogs naturally infected by Leishmania in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 84 publications
0
16
0
2
Order By: Relevance
“…In a previous study [11] on this nutraceutical, we showed an immunomodulating activity that did not provide an exhaustive explanation of the clinical improvement. For these reasons, in this study we explored the possible effects of DìLsh TM on inflammatory and oxidative stress markers of 15 CL infected dogs, as compared with 10 CL dogs treated with anti-leishmanial therapy at diagnosis and during a three-month follow-up.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…In a previous study [11] on this nutraceutical, we showed an immunomodulating activity that did not provide an exhaustive explanation of the clinical improvement. For these reasons, in this study we explored the possible effects of DìLsh TM on inflammatory and oxidative stress markers of 15 CL infected dogs, as compared with 10 CL dogs treated with anti-leishmanial therapy at diagnosis and during a three-month follow-up.…”
Section: Introductionmentioning
confidence: 62%
“…The similarity of the beneficial effects of both treatments in improving a leishmaniotic dog's quality of life seems to be the results of the different mechanisms by which the two treatments act on their global health, impairing the protozoa responsible for the disease. By lowering the protozoa activity, the conventional therapy was much more effective than DìLsh TM in reducing the negative effects due to the increase of some pro inflammatory molecules; on the other hand, together with the immune-modulating activity described by Lombardi et al [11], the positive antioxidant effect of DìLsh TM may exert important beneficial effects on a dog's health status, finally resulting in similar clinical and clinicopathological results between the two treatments.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some nutraceuticals (e.g., Anxitane ® , which contains the active ingredient l-theanine; or Solliquin ® , which includes L-theanine and two plants derived extracts, Phellodendron amurense and Magnolia officinalis ; and Zylkene ® , which contains the active ingredient alpha-casozepine) and diets with some of these ingredients have a documented anti-anxiety effect, without side effects [ 28 ]. Moreover, many attempts to identify the active components of herbal remedies have concluded that, in general, no one component is responsible for the therapeutic capacity, but rather a complex and intricate interaction of various herbs may result in therapeutic efficacy [ 29 , 30 ]. Recently, DìRelax TM has been part of the nutraceutical products and has a proven clinical efficacy (BIBL) without presenting side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, immunotherapy should contribute to drug sparing, combating drug re-sistance, and reducing the side effects of several therapeutic agents [2]. Nucleotides have been included within the choices of effective immunotherapies for the management and control of CanL in recently published articles [121,191], and other examples of nutritional modulation of the immune response with promising results in leishmaniasis also exist [192][193][194][195].…”
Section: The Role Of Nucleotides In Canl Multimodal Managementmentioning
confidence: 99%